A Novel Coherent Digital Sweep Oscillator with Extremely Low Sweep Rates and Harmonic Distortion. (2001) - Al-Ibrahim (Jarrah), M. M.
Abstract : A novel technique to efficiently increase the resolution of coherent digital sweep oscillators based on look-up-table (LUT) methods is proposed. The increase in resolution measured in terms of sweep rates is achieved while maintaining very low levels of spurious harmonic distortion. The proposed technique increases the LUT length to a level at which the spurious harmonic distortion is negligible. The proposed technique is based on partitioning the address register into three sets and dividing the available LUT length into five smaller tables addressed according to the content of the three address register sets. The proposed technique is simulated and its performance is compared with that of the known sweep oscillators. The simulation results show that the proposed technique is superior to all sweep oscillators reported in the literature.